KARYA-KARYA TARALAMSYAH SARAGIH SEBAGAI KOREOGRAFER TARI SIMALUNGUN - ANTIN LESTARI (Gesture: Jurnal Seni Tari, 2014)
This research is a study of the choreographic form in Saragih Taralamsyah’s works as Simalungun dance choreographer. The aim of this study is to describe the choreographic form in Saragih Taralamsyah’s works as Simalungun dance choreographer In the discussion of this research, the theories related to the topic of research used are the biographical understanding, the form theory, the identity theory, and the theory of choreography. In conducting this research, the writer uses descriptive qualitative method. The population in this study becomes the sample of the research which is Taralamsyah Saragih’s works. Data collection techniques consist of literature studies, interviews, observation, and documentation. According to the research, it can be concluded that Taralamsyah Saragih is one of the artists from Simalungun. He’s a son of the 40th King Raya who was born in Pematang Raya Simalungun Bolon’s House on August 18th 1918. The form of choreographic dances as Haroan Bolon tortor, Sitalasari tortor, Manduda tortor created by Taralamsyah can be seen from the function, the pattern of cultivation and choreography. Characteristic contained in Saragih Taralamsyah works can also be seen from the side of the theme, movement, music, costumes, pattern of the floor, and the number of dancers. Instruments used in the works of Taralamsyah Saragih are accordion, sulim, flute, keyboards, guitar, piano, cymbals and gondrang sipitu-pitu. Keywords: Choreographic Form, Works, Taralamsyah Saragih.